Intentional Abuse of Social Networks with the Goal of Promoting Ideas of Anti-Semitism, Racism, and Xenophobia - Slivka, Daniel; Mierzwa, Janusz (Communications - Scientific letters of the University of Zilina, 2017)
This scientific study points out a relatively common negative occurrence in the Slovak society as well as in Europe in general. Various parties, associations and movements, most notably on the extreme right side of the spectrum, use virtual social networks to promote their ideals and to reach their goals in the society. Social networks often contain hidden and manipulative forms of promoting ideas of anti-Semitism, racism, and xenophobia.